Příklady z matematiky

             ( x+4)( y-2) = ( x-5)( y+4)

             ( x+6)( y-1) = ( x-1)( y+2)

              xy-2x+4y-8=xy+4x-5y-20

              xy -x+6y -6=xy+2x –y -2

                   -6x + 9y = -12

                   -3x + 7y = 4   / (-2)

                   -6x + 9y = -12

                   6x – 14y = -8

                           - 5y = -20

                                y = 4

 

x =                       = 8

 

 

L1 = (8+4)(4-2) = 12.2 = 24

P1 = (8-5)(4+4) = 3.8 = 24

 

L2 = (8+6)(4-1) = 14.3 = 42

P2 = (8-1)(4+2) = 7.6 = 42

 

 

 

                                 P = [ 8;  4 ]